Thermodynamic Analysis of Massic Heat Capacity in Bovine Species - Khalifa, Giana Ibrahiem (Journal of Research in Vocational Education, 2025)
This study investigates the specific heat capacity of femur, rib, and scapula bones from ox and camel under normal and decalcified conditions using Renault's apparatus, which operates on the principle of the method of mixtures. The results indicate a decrease in specific heat after decalcification, with variations observed among different bones and species. The study highlights the influence of calcium phosphate on the thermal properties of bones, providing insights into the thermal regulation mechanisms in living organisms. The method employed is described as simple, elegant, inexpensive, and accurate.